KARAKTERIK GETARAN PONDASI MESIN INDUK OFFSHORE SUPPLY VESSEL 907 GT PADA KONDISI OPERASI - Poernomo, Heroe; Husodo, Adi Wirawan; Soim, Subagio; Antoko, Bambang; Ariwiyono, Nopem; Alhakim, Rizaldi Taufik (Politeknik Negeri Madura, 2023)
In this research, an analysis has been carried out to determine the vibration characteristics that occur on the main engine foundation of the 907 GT offshore supply ship under operating conditions. Numerical methods based on mathematical modelling of machine foundation construction are used as a reference for analysing the possibility of resonance, displacement response and velocity response. Mathematical modelling is developed by taking into account the weight and power of the main engine, the dimensions and configuration of the main engine foundation, and the damping coefficient. Mathematical modelling is realized in the form of a 2nd order differential equation (ODE). From the results of the analysis performed, it shows that resonance generally does not occur. This is because the value of the natural frequency of the main engine foundation is different from the value of the engine excitation frequency. However, more attention must be paid when the ship operates at engine speed between 1760 RPM to 1980 RPM. This is because the value of the main engine excitation frequency is close to the natural frequency of the foundation construction. The greater the rotation of the main engine, the magnitude of the displacement response is also greater. The velocity response value that occurs still meets the conditions specified by the American Bureau of Shipping (ABS). Mathematical modelling that has been prepared can describe clearly the vibration characteristics of the main engine foundation.